Epidemics and the Health of African Nations - Mazibuko, Zamanzima (Jacana Media, 2019)
"Epidemics and the Health of African Nations, explores Africa's vulnerability to disease, and demonstrates that this disease occurs commonly because of political and economic influences. These factors also determine the way epidemics are managed and controlled. News footage of epidemics and disease in Africa is a familiar sight. Yet these outbreaks are often presented without reference to the preceding events and conditions that have triggered them. Authors extract lessons from case studies in different parts of Africa; challenge conventional frameworks about disease to argue for a multi-faceted 'syndemics' approach that takes account of the interrelationship between disease and political and socioeconomic contexts; examine the factors affecting the efficacy of frontline healthcare workers and point to the diseases and health challenges of Africa's future. A key argument is that a well-functioning health system is at the core of a country's capacity to provide quality healthcare to counter an epidemic. Authors argue that it would be more productive to mobilise resources to build strong health systems across Africa than to mobilise international resources in a panicked response to an outbreak. Alongside this, a case is made for the equally important need to address the structural drivers of vulnerability to diseases. It is futile to treat patients who will return home to poor nutrition and inadequate water services that will expose them again to disease. This volume brings African experts together to probe possible solutions to the continent's heavy burden of disease. The recurring themes in this book and the insights extracted from individual case studies will be helpful in devising policy for the control of disease and the combatting of epidemics in Africa."